Effect of number and arrangement of separator electrode assembly (SEA) on the performance of square tubular PEM fuel cells. (15th October 2017) - Mohammadi-Ahmar, Akbar; Solati, Ali; Osanloo, Behzad; Hatami, Mohammad
Abstract: The effect of intermediate electrode on the performance of the square tubular PEMFC was studied in the present paper. Four different configurations were developed and evaluated for the first time, namely: simple square tubular (without intermediate electrode i.e. Simple), double parallel intermediate electrode (DPIE), double bisectors intermediate electrode (DBIE) and triple parallel intermediate electrode (TPIE). Calculations were performed maintaining the same active area and boundary conditions for all four configurations. The results of polarization curves showed that the insertion of the intermediate electrode increases current density, and leads to higher consumption of reactants and better performance of PEMFC. Employing the intermediate electrode not only does not cause any additional cost compared to simple square tubular configuration, but also the cost is reduced in comparison to the base model due to the reduction of fuel cell length. The results also revealed that the intermediate electrode arrangement also has a significant influence on the performance of PEM fuel cell; For instance, DPIE compared to DBIE delivers higher power and has better performance. Moreover, it was proved that the addition of more than one intermediate electrode layer increases the pressure drop dramatically which fades the advantage of increasing power output. Highlights: The performance of PEM fuel cell is numerical simulated. CFD study on reactants distribution, current density and final power was performed. Four square tubular configurations were investigated (simple, DPIE, DBIE and TPIE). DPIE configuration showed better performance compared to the DBIE. Adding more than one intermediate electrode layer decreases the net output power.